A Morphological Study of Aesthetic Styles in Spider-Man Animated Series and Film Adaptations (Cinematology: Journal Anthology of Film and Television Studies, 2025)
To this day, many still perceive animation merely as a product for children, a perspective that motivated the push for the movement of “animation is cinema.” Driven by this movement, this research focuses on the artistic and technological evolution of animation through three Spider-Man adaptations, each representing a different era: Spider-Man (1967), Spider-Man: The New Animated Series (2003), and Spider-Man: Across the Spider-Verse (2023). Using a qualitative method with a content analysis approach, this research examines the three works through the frameworks of animation aesthetic morphology, and also Paul Wells’ classification of animation styles. The results of the study show a clear progression from one work to another, with each possessing its own characteristics and identity that represent the era in which they were made. The development of animation, as represented by the aesthetics of these three objects, affirms that animation is a medium of boundless artistic expression. So with this article, the researcher hopes could help those who read it to better understand animation capabilities as a medium.